2010
DOI: 10.1007/s00464-010-0888-2
|View full text |Cite
|
Sign up to set email alerts
|

Extraluminal laparoscopic wedge resection of gastric submucosal tumors: a retrospective review of 84 cases

Abstract: ELWR is a safe, simple, and effective procedure for treating submucosal tumors in the upper part of the stomach. It can avoid intraperitoneal contamination, possible tumor spillage, and postoperative esophageal stenosis, and provides unlimited scope for gastric resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Currently, submucosal myogenic tumors, including leiomyoma and stromal tumors as described in this study, are mainly treated by conventional methods such as open surgery or laparoscopic excision [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, submucosal myogenic tumors, including leiomyoma and stromal tumors as described in this study, are mainly treated by conventional methods such as open surgery or laparoscopic excision [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, laparoscopic wedge resection is an approach that could be performed widely, but more data still are needed to assess its safety and utility for patients with stromal gastric tumors. Therefore, the report by Ke et al [1] and analysis of their data merit our consideration. Ke et al [1] retrospectively identified 84 patients who underwent extraluminal laparoscopic wedge resection for gastric submucosal tumors between Sep 2000 and Dec 2007 and analyzed the clinical, pathologic, and follow-up data for these patients.…”
mentioning
confidence: 96%
“…Therefore, the report by Ke et al [1] and analysis of their data merit our consideration. Ke et al [1] retrospectively identified 84 patients who underwent extraluminal laparoscopic wedge resection for gastric submucosal tumors between Sep 2000 and Dec 2007 and analyzed the clinical, pathologic, and follow-up data for these patients. All of the procedures were successfully performed with a mean operation time of 62.6 min.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In our early experience (1997-1999), we had about a 10.5% (2/19) rate for postoperative complications such as esophagostenosis and gastric incision leakage, which urged us to explore a novel strategy for treating submucosal tumors. Since 2000, we have used ELWR to treat GISTs in the upper part of the gastric body and in the gastric fundus [4].…”
mentioning
confidence: 99%